2022
DOI: 10.1080/17445302.2022.2140531
|View full text |Cite
|
Sign up to set email alerts
|

A review of challenges and framework development for corrosion fatigue life assessment of monopile-supported horizontal-axis offshore wind turbines

Abstract: Digital tools such as machine learning and the digital twins are emerging in asset management of offshore wind structures to address their structural integrity and cost challenges due to manual inspections and remote sites of offshore wind farms. The corrosive offshore environments and salt-water effects further increase the risk of fatigue failures in offshore wind turbines. This paper presents a review of corrosion fatigue research in horizontal-axis offshore wind turbines (HAOWT) support structures, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Literature also showcases applications more focused on fault detection. Okenyi et al (2022) delve into the application of ANN within digital twin systems for offshore wind turbines, particularly highlighting their efficacy in fault detection. They emphasize that ANN, alongside other ML techniques, excels in tracing patterns in fault diagnosis, crucial for addressing challenges in corrosion fatigue assessment.…”
Section: Module 4: Ai-driven Diagnosis and Remedial Action Recommenda...mentioning
confidence: 99%
“…Literature also showcases applications more focused on fault detection. Okenyi et al (2022) delve into the application of ANN within digital twin systems for offshore wind turbines, particularly highlighting their efficacy in fault detection. They emphasize that ANN, alongside other ML techniques, excels in tracing patterns in fault diagnosis, crucial for addressing challenges in corrosion fatigue assessment.…”
Section: Module 4: Ai-driven Diagnosis and Remedial Action Recommenda...mentioning
confidence: 99%
“…2. A strain gauge capable of recording a high sample rate was connected to the InstruNET [19] data acquisition system. For each test, a sample rate of 1666.7 samples/secs and a two-flute cutting tool with a diameter of 10 mm were used.…”
Section: Verification Of Fatigue Testing Using Millingmentioning
confidence: 99%
“…A comprehensive review of ML-based offshore wind farm condition monitoring techniques can be found in [83]. Exploring the landscape of corrosion fatigue assessment in horizontal-axis offshore wind turbines, Okenyia et al advocated the potential of digital twins, amalgamating finite element analysis, material modeling, artificial neural networks, data analytics, and Internet of Things (IoT) with sensor technologies to address challenges in shallow and deep water installations [84]. Additionally, Pezeshki and colleagues conducted an extensive literature review on structural health monitoring for offshore and marine structures, considering the prospect of ML implementations [85].…”
Section: Health Monitoring and Maintenancementioning
confidence: 99%